Preparation method of rubber material for tire and tire containing rubber material

By combining ionic iron with white fillers, oxygen bridges and chelates are formed to replace zinc oxide activators, the problems of zinc pollution and low catalytic activity are solved, and the effects of rapid vulcanization and high mechanical properties are achieved in the low temperature. .

CN119317661APending Publication Date: 2025-01-14PIRELLI TYRE SPA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380043800.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-08
Filing Date
2023-06-05
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The zinc oxide used in the existing tire industry as a vulcanization activator has the risk of environmental pollution and is difficult to completely replace, and other metal oxides have low catalytic activity, which affects the efficiency of vulcanization reaction and crosslinking density.

Method used

Iron in ionic form is combined with white fillers such as silica through coupling agents to form oxygen bridges and chelates to replace zinc oxides and improve vulcanization reaction efficiency and mechanical properties.

Benefits of technology

It achieves rapid vulcanization at low temperature without using silane, improves vulcanization time and mechanical properties, reduces zinc pollution, and has environmentally friendly advantages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160279350000241
    Figure BDA0005160279350000241
  • Figure BDA0005160279350000251
    Figure BDA0005160279350000251
  • Figure BDA0005160279350000271
    Figure BDA0005160279350000271
Patent Text Reader

Abstract

The present invention relates to a compound represented by formula (II): WF-O-ROS-GC-Fe (II) wherein WF represents a white filler, O represents one or more oxygen bridged bonds, ROS represents an organosilane residue, GC represents one or more coordinating groups forming a chelate with iron in ionic form, Fe represents one or more oxygen bridged bonds, Fe represents one or more oxygen bridged bonds, Fe represents one or more oxygen bridged bonds, Fe represents one or more oxygen bridged bonds, Fe represents one or more oxygen bridged bonds, Fe represents one or more coordination groups forming a chelate with iron in ionic form, Fe represents one or more oxygen bridged bonds, and Fe represents one or more coordination groups forming a chelate with iron in ionic form. And Fe represents iron in ionic form (Fe < 3 + >) coordinated to a coordination group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing an elastomeric rubber compound for tires, the rubber compound can be effectively vulcanized without introducing zinc, and is characterized in that a specific modified filler capable of activating the vulcanization is incorporated.

[0002] Have technology

[0003] In the tire industry, vulcanization is a method commonly used to improve the mechanical properties of natural rubber or unsaturated polymers, affecting the material's hardness, elasticity, hysteresis at different temperatures and, therefore, the tire's behavior in wet conditions and its friction and wear during use.

[0004] Over the years, various additives have been proposed as vulcanization activators and accelerators to improve the vulcanization process.

[0005] Generally, with these additives, it is desired to increase the extent and uniformity of crosslinking while reducing the energy and time required to complete the reaction.

[0006] The main sulfurization activators capable of improving the efficiency of the process are inorganic compounds such as metal oxides and hydroxides, for example ZnO, MgO, Ca(OH)2.

[0007] Among the different activators, zinc oxide ZnO is considered the most effective and is still used in many vulcanization processes. This activator is used in combination with a weak organic acid (such as stearic acid) that promotes its activity in rubber.

[0008] The poor dispersibility and reactivity of microcrystalline zinc oxide in elastomeric compounds inevitably lead to an excess thereof relative to the amount actually required for crosslinking.

[0009] Since zinc can contaminate land and water used for agricultural purposes, a phenomenon that can cause serious damage to animal and plant species and ultimately to humans through accumulation, attempts have been made over the years to reduce the amount of zinc in rubber compounds and, therefore, the amount dispersed in the environment due to normal wear of tires.

[0010] Initially, it has been shown to be advantageous to use materials in which the silica surface has been functionalized with aminosilanes, such as 3-aminopropyl-triethoxysilane (APTES), which bind to the silica surface via covalent bonds of the Si-O-Si type, which results in the terminal amino groups of the aminosilanes reacting with the Zn 2+The use of these new materials in the vulcanization process of elastomeric rubbers has demonstrated higher vulcanization efficiency and better crosslink density than conventionally used ZnO activators, as described in WO 2020 / 110023 in the name of the applicant, and in "Design of a Zn Single-Site Curing Activator for a More Sustainable Sulfur Cross-Link Formation in Rubber" Ind. Eng. Chem. Res. 2021, 60, 10180-10192 by S. Mostoni et al.

[0011] Subsequently, in an attempt to completely replace the use of zinc, the use of other metal oxides (such as CaO, MgO, BaO, BeO and CuO) instead of zinc oxide as activators for the vulcanization of EPDM and SBR rubbers was studied (Lautenschlaeger, fk; Edwards, k. Model compound vulcanisation-part V. The effect of chemical additives and fillers. Rubber Chem. Technol. 1979; Vol. 53; 27-47).

[0012] Other studies conducted to compare the catalytic activity of calcium oxide and magnesium oxide in the vulcanization reaction have shown that when calcium oxide is used as an activator, the kinetics are slower and a lower degree of crosslinking is achieved. When magnesium oxide is used instead of ZnO, the accelerator reacts with good kinetics in the first step of the vulcanization reaction, but in this case, a lower crosslinking density is achieved than that obtained with zinc oxide. In this case, zinc oxide remains the best activator, resulting in a high degree of crosslinking (Roy, K.; Alam, MN; Mandal, SK; Debnath, SCP Reparation of zinc-oxide-free natural rubber nanocomposites using nanostructured magnesium oxide as cure activator. J. Appl. Polym. Sci. 2015, 132, 1-7); (Guzmán, M.; Vega, B.; Agulló, N.; Giese, U.; Borrós, S. Zinc oxide versus magnesium oxide revisited. Part 1. Rubber Chem. Technol. 2012, 85, 38–55;) (Guzmán, M.; Vega, B.; Agulló, N.; Borrós, S. Zinc Oxide Versus Magnesium Oxide Revisited. Part 2. Rubber Chem. Technol. 2012, 85, 56-67).

[0013] Some research has been done on the use of iron, especially in the form of iron oxide, in elastomeric compounds to impart certain properties to the final material, such as magnetic, electrical or conductive properties, or to influence the cross-linking reaction.

[0014] El-Nashar et al. [J Mater Sci (2006) 41, 5359-5364] prepared composites with good mechanical, magnetic and electrical properties by mixing different concentrations of magnetic Fe nanoparticles as fillers with a natural rubber matrix to form composites for different applications.

[0015] Bellucci et al. [Composites Part B: Engineering, Vol. 85 (2016) 196-206] studied the effects of size, shape and concentration of ferrite nanoparticles on the magnetic properties of natural rubber nanocomposites.

[0016] Smejda-Krzewicka et al. [Iranian Polymer Journal (2019) 28: 313-323] studied the effect of iron (III) oxide (Fe2O3) in the crosslinking process of chloroprene butadiene rubber (CR / BR) compounds and observed that the resulting CR / BR / Fe2O3 vulcanization products were characterized by good mechanical properties, higher hardening speed and high fire resistance.

[0017] Dziemidkiewicz et al. [Journal of Thermal Analysis and Calorimetry (2019) 138: 4395-4405] studied the activity of metal acetylacetonates, especially iron acetylacetonate, as vulcanizing agents for brominated butyl rubber (BIIR) based on the Heck-type reaction.

[0018] Tantawy et al. (Polym Int 49, 1670-1676 (2000)) studied the effect of the combination of iron oxide (Fe3O4) with zinc oxide and carbon black on the vulcanization process of butyl rubber (IIR) by measuring DC conductivity, thermoelectric power, dielectric constant and IV characteristics. SUMMARY OF THE INVENTION

[0020] The Applicant has conducted research to further improve the effectiveness of activated fillers in the production of rubber compounds for tires, with the aim of eliminating zinc incorporated into the compound, with important benefits for the environment, without deteriorating or even improving its properties compared to comparable conventional compounds.

[0021] Surprisingly, the applicants have found that the ionic form of Fe 3+ The iron can be bound to white filler particles, such as silica nanoparticles, by a coupling agent comprising a reactive group capable of binding to the surface of the white filler, in particular capable of forming an oxygen bridge, and a coordinating group capable of chelating the iron in ionic form.

[0022] Therefore, the coupling agent can be represented by the following formula (I):

[0023] GR-ROS-GC (I)

[0024] Wherein GR represents one or more reactive groups capable of bonding to the surface of the white filler by forming an oxygen bridge (—O—), ROS represents an organo-silane residue, and GC represents one or more coordinating groups.

[0025] Furthermore, the material produced by the applicant can thus be schematically represented by the following formula (II):

[0026] WF-O-ROS-GC-Fe (II)

[0027] The reactive groups GR react with the surface of the white filler (WF) to form oxygen bridges (—O—) with organo-silane residues (ROS), and the coordinating groups GC then chelate the iron in ionic form.

[0028] The applicant has surprisingly found that this material offers various advantages when used in the vulcanization process of rubber compounds used in the production of tires.

[0029] Advantageously, the use of such materials makes iron readily available in ionic form, allowing for faster and more efficient formation of the organometallic complex.

[0030] The Applicant has observed that the use of such materials allows the use of lower mixing temperatures since they do not require the use of silanes, with all the advantages of material integrity and preparation costs of the elastomeric compound to be subjected to vulcanization.

[0031] Furthermore, the Applicant has observed that such a material allows faster vulcanization times and better mechanical properties of the resulting vulcanized material.

[0032] A further advantage observed by the Applicant is the fact of eliminating the use of zinc in the tyre vulcanization process, with clear advantages from an environmental point of view.

[0033] Therefore, the first aspect of the present invention is a compound represented by the following formula (II):

[0034] WF-O-ROS-GC-Fe (II)

[0035] wherein WF represents a white filler, O represents one or more oxygen bridges, ROS represents an organo-silane residue, GC represents one or more coordinating groups that form a chelate with the ionic form of iron, and Fe represents the ionic form (Fe 3+ ) of iron.

[0036] The second aspect of the present invention is represented by a method for preparing a compound represented by formula (II) according to the first aspect of the present invention, wherein the method at least comprises:

[0037] Provide white filler (WF),

[0038] Providing a coupling agent having the following formula (I):

[0039] GR-ROS-GC (I)

[0040] wherein GR represents one or more reactive groups capable of forming an oxygen (—O—) bridge with the surface of the white filler, ROS represents an organo-silane residue, and GC represents one or more coordinating groups,

[0041] Provided in ionic form (Fe 3+ ) of the iron precursor,

[0042] reacting a white filler (WF) with one or more reactive groups (GR) in the compound of formula (I) to form an oxygen (—O—) bridge between the white filler and the organo-silane residue (ROS),

[0043] · Make one or more coordination groups (GC) in the compound of formula (I) and ionic form (Fe 3+ ) to form a chelate, and

[0044] • Isolate the obtained compound of formula (II) WF-O-ROS-GC-Fe.

[0045] A third aspect of the invention is represented by a method for preparing a vulcanizable elastomeric compound for a tire, wherein said method comprises at least:

[0046] a mixing step (1) of at least one elastomeric polymer and at least one additive for an elastomeric compound (other than a vulcanizing agent) to obtain a non-vulcanizable elastomeric compound;

[0047] a mixing step (2) of said non-vulcanizable elastomeric compound and at least one vulcanizing agent to obtain a vulcanizable elastomeric compound, and

[0048] · Steps for unloading the vulcanizable elastomeric compound,

[0049] The compound according to the first aspect of the present invention is added in at least one of the mixing steps (1) and (2).

[0050] A fourth aspect of the invention is represented by a vulcanizable elastomeric compound obtainable by the process according to the third aspect of the invention.

[0051] The fifth aspect of the present invention is a component for a tire, comprising the vulcanizable rubber compound of the fourth aspect of the present invention or a vulcanized rubber compound obtained by vulcanizing the same.

[0052] A sixth aspect of the present invention is a tire for a vehicle wheel, comprising the component according to the fifth aspect of the present invention.

[0053] definition

[0054] For the purposes of the present description and of the following claims, the term “phr” (parts per hundred parts of rubber) refers to the parts by weight of a given component of the elastomeric composition relative to 100 parts by weight of the diene elastomeric polymer.

[0055] Unless otherwise indicated, all percentages are expressed as weight percent.

[0056] As used herein, the term "elastomeric polymer" or "rubber" or "elastomer" refers to a natural or synthetic polymer which, after vulcanization, can be repeatedly stretched to at least twice its original length at room temperature and which, upon removal of the tensile load, recovers substantially immediately to about its original length under force (as defined in ASTM D1566-11 Standard Terminology Relating to Rubber).

[0057] In the present description, the term "reinforcing filler" refers to reinforcing materials commonly used in the field to improve the mechanical properties of tire rubber, preferably selected from carbon black, conventional silica, for example silica from sand precipitated with strong acids, preferably amorphous, diatomaceous earth, calcium carbonate, titanium dioxide, talc, aluminum oxide, aluminosilicates, kaolin, silicate fibers and mixtures thereof.

[0058] In this specification, the term "white filler" refers to conventional reinforcing materials used in the art, which are selected from conventional silica and silicates, such as sepiolite, palygorskite (also known as attapulgite), montmorillonite, halloysite, etc., which may be modified and / or derivatized by acid treatment. Typically, white fillers have surface hydroxyl groups.

[0059] In the present specification, the term "reactive group" refers to a group capable of reacting with the surface hydroxyl group of the white filler to form an oxygen bridge (-O-) and eliminate water or alcohol, usually a hydroxyl group (-OH) or an alkoxy group (-OR), wherein R represents a straight or branched alkyl chain having 1 to 6 carbon atoms.

[0060] In the present specification, the term "organo-silane residue" refers to a residue comprising at least one linear or branched alkyl chain having 1 to 6 carbon atoms bonded to a silicon atom.

[0061] In this specification, the term "coordinating group" refers to a group that can bind to Fe in ionic form. 3+ The iron forms a coordination bond with an atom such as nitrogen, oxygen or sulfur functional group.

[0062] In this specification, the term "ionic form (Fe 3+ )” refers to a compound selected from the group consisting of Fe2O3, Fe(OH)3 and Fe 3+ of organic or inorganic salts.

[0063] In the present description, the term "elastomeric compound" means a product obtained by mixing and optionally heating at least one elastomeric polymer with at least one additive usually used in the preparation of tire compounds.

[0064] In this specification, the term "non-vulcanizable elastomeric compound" means a product obtained by mixing at least one elastomeric polymer with at least one additive (except a vulcanizing agent) conventionally used in the preparation of tire compounds. The non-vulcanizable elastomeric compound may also be referred to as phase (1) elastomeric compound.

[0065] In this specification, the term "vulcanizable elastomeric compound" refers to an elastomeric compound ready for vulcanization, into which all additives including vulcanizing additives have been incorporated. The vulcanizable elastomeric compound may also be referred to as phase (2) elastomeric compound.

[0066] In the present specification, the term "vulcanized elastomeric compound" means a material obtained by vulcanization of a vulcanizable elastomeric compound.

[0067] In the present description, the term "mixing step (1)" denotes the step of the process for producing an elastomeric compound in which one or more additives other than those vulcanizing additives fed in step (2) can be incorporated by mixing and possibly heating.

[0068] In the present specification, the term "mixing step (2)" denotes a subsequent step of the process for producing the elastomeric compound, in which the vulcanizing agent and preferably the vulcanization accelerator and / or the retardant are introduced and mixed in the material at a controlled temperature, generally at a mixing temperature below 160°C.

[0069] The mixing step (1) is also called a "non-productive step" because the components of the rubber compound, except those for crosslinking (eg sulphur and accelerators), are fed into the mixing device.

[0070] The mixing step (2) is instead referred to as the production step. In this step, the elastomeric compound obtained from step (1) and the vulcanization additives capable of promoting and / or controlling crosslinking are fed into a mixing device to provide a vulcanizable elastomeric compound.

[0071] In this specification, the term "green" is generally used to refer to a material, compound, composition, component or tire that has not yet been vulcanized. DETAILED DESCRIPTION OF THE INVENTION

[0073] The process for preparing the compound of formula (II) of the present invention will be described in detail below.

[0074] The process is characterized by one or more of the following preferred aspects alone or in combination with each other, in particular by using a coupling agent having the following formula (I):

[0075] GR-ROS-GC (I)

[0076] wherein GR represents one or more reactive groups, ROS represents an organo-silane residue, and GC represents one or more coordinating groups.

[0077] The method of the present invention at least comprises:

[0078] Provide white filler (WF),

[0079] Providing a coupling agent having the following formula (I):

[0080] GR-ROS-GC (I)

[0081] wherein GR represents one or more reactive groups capable of forming an oxygen (—O—) bridge with the surface of the white filler, ROS represents an organo-silane residue, and GC represents one or more coordinating groups,

[0082] Provided in ionic form (Fe 3+ ) of the iron precursor,

[0083] reacting a white filler (WF) with one or more reactive groups (GR) in the compound of formula (I) to form an oxygen (—O—) bridge between the white filler and the organo-silane residue (ROS),

[0084] · Make one or more coordinating groups (GC) in the compound of formula (I) and ionic form (Fe 3+ ) to form a chelate, and

[0085] • Isolate the obtained compound of formula (II) WF-O-ROS-GC-Fe.

[0086] The white filler may be any conventional white reinforcing filler having hydroxyl groups on the surface.

[0087] The white filler is preferably selected from conventional silicas and silicates in the form of fibers, flakes or particles, for example bentonite, nontronite, beidellite, volkonite, hectorite, saponite, sauconite, vermiculite, sericite, sepiolite, palygorskite (also known as attapulgite), montmorillonite, halloysite and the like, which may be modified and / or derivatized by acid treatment, and mixtures thereof, more preferably it is silica.

[0088] The shape, specific surface area and size of the silica can vary.

[0089] Examples of silica are pyrogenic silica, precipitated amorphous silica, wet silica (hydrated silicic acid) or mixtures thereof.

[0090] An example of a suitable commercially available silica is the precipitated silica Rhodia Zeosil MP1165 (BET surface area 160 m 2 / g), Ultrasil VN3 GR (BET specific surface area 180m2 / g) and Zeosil 1115MP (BET surface area 95-120m 2 / g).

[0091] Preferably, the specific surface area (BET) of the silica is at least 120 m 2 / g, more preferably at least 140m 2 / g.

[0092] Preferably, the specific surface area (BET) of the silica is less than 220 m 2 / g, more preferably less than or equal to 180m 2 / g.

[0093] A useful example of the compound represented by formula (I) is an alkoxysilane functionalized with one or more heteroatom-containing functional groups, wherein the alkoxy group represents a reactive group GR capable of bonding to the white filler, and the heteroatom-containing functional group represents a reactive group GR capable of bonding to the ionic form (Fe 3+ )'s iron forms a coordination bond with the coordination group GC.

[0094] Preferred examples of the reactive group GR are alkoxy groups having 1 to 4 carbon atoms, namely methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy and tert-butoxy groups.

[0095] Preferred examples of GC coordinating groups represented by functional groups containing heteroatoms are linear or branched alkyl chains containing one or more heteroatoms within or at the ends of the alkyl chains, such as functional groups represented by the formula: -C n H 2n -XC m H 2m -Y or -C m H 2m -Y, wherein n and m are the same as or different from each other and are an integer from 1 to 6, inclusive; X is a group selected from a thiol group and an amino group, and Y is a group selected from a thiol group, an amino group, a dithiocarbamate group and a carboxyl group.

[0096] Useful examples of the compound represented by formula (I) are represented by the following general formulae (Ia) and (Ib):

[0097] (R)3Si-C n H 2n -XC m H 2m -Y (Ia)

[0098] (R)3Si-C m H 2m -Y (Ib)

[0099] wherein the R groups are the same as or different from each other and are selected from alkyl or alkoxy groups having 1 to 4 carbon atoms, provided that at least one of the R groups is an alkoxy group; n and m, which are the same as or different from each other, are integers from 1 to 6, inclusive; X is a group selected from thiol and amino, and Y is a group selected from thiol, amino, dithiocarbamate and carboxyl.

[0100] Compounds useful in the present invention are (3-aminopropyl)triethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyl-trimethoxysilane (also known as N-[3-(trimethoxysilyl)propyl]ethylenediamine (EDTMS)), N-(2-aminoethyl)-3-aminopropyl-triethoxysilane, N-(2-aminoethyl)-3-aminopropyl-methyl-dimethoxysilane, 3-aminopropylmethyl-diethoxysilane, 3-ureidopropyl-trimethoxysilane, 3-ureidopropyl-triethoxysilane, N-cyclohexyl(aminomethyl)methylthiosilane, N-cyclohexyl(aminomethyl)triethoxysilane, N-cyclohexyl-3-aminopropyl-trimethoxysilane, 3-(2-aminomethylamino)propyl-triethoxysilane, N-(n-butyl)- trimethoxysilane, N,N-diethylaminopropyl-trimethoxysilane, N,N-dimethylaminopropyl-trimethoxysilane, butylaminomethyl-triethoxysilane, N-cyclohexyl(aminomethyl)trimethoxysilane, 2-aminoethylaminomethyl-triethoxysilane, diethylaminomethyl-triethoxysilane, (3-mercaptopropyl)triethoxysilane and (3-mercaptopropyl)trimethoxysilane.

[0101] Preferred compounds are (3-mercaptopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane (APTES), (3-aminopropyl)trimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (also known as N-[3-(trimethoxysilyl)propyl]ethylenediamine (EDTMS)), and N-(2-aminoethyl)-3-aminopropyltriethoxysilane.

[0102] Ionic form (Fe 3+ ) can be Fe2O3, Fe(OH)3, Fe 3+organic or inorganic salts thereof, such as anhydrous or hydrated ferric nitrate, ferric sulfate, ferric carbonate, ferric chloride, ferric bromide, ferric iodide, ferric fluoride, ferric phosphate, ferric acetate, ferric oxalate, ferric citrate, ferric gluconate, ferric fumarate, ferric lactate, and the like.

[0103] The reaction step between the white filler and the coupling agent of formula (I) is carried out thermally in a solvent phase by first dispersing the white filler in a suitable solvent and then adding the coupling agent and allowing it to react until the reaction is complete.

[0104] The solvent used for the reaction is preferably selected from non-polar solvents such as hexane, cyclohexane, benzene and toluene.

[0105] Optionally, the white filler is first activated by being dispersed in an alkaline aqueous solution (e.g., sodium hydroxide solution). The activation of the white filler is carried out at least 1 hour, more preferably at least 3 hours, even more preferably at least 6 hours at room temperature in the range of 20° C. to 30° C. The activation time period is preferably less than 48 hours, more preferably less than 36 hours. Advantageously, the activation time period ranges from 12 hours to 24 hours. The white filler activated in this way is separated by conventional separation techniques (filtration, centrifugation, etc.), and then freeze-dried.

[0106] The reaction between the white filler and the coupling agent is preferably carried out at a temperature above 40° C., more preferably above 60° C., even more preferably above 80° C. The reaction temperature is preferably below 200° C., more preferably below 180° C., even more preferably below 160° C.

[0107] The reaction between the white filler and the coupling agent is preferably carried out at the reflux temperature of the reaction mixture for at least 1 hour, more preferably at least 3 hours, and even more preferably at least 6 hours. The reaction time period is preferably less than 48 hours, more preferably less than 36 hours. Advantageously, the reaction time ranges from 12 to 24 hours.

[0108] The reaction product represented by the functionalized white filler is isolated by conventional separation techniques (filtration, centrifugation, etc.) and then dried at a temperature of 60°C to 100°C.

[0109] The functionalized white filler represented by the formula WF-O-ROS-GC is then reacted with an ionic form (Fe 3+ ) to form a chelate represented by formula (II).

[0110] The functionalized white filler (WF-O-ROS-GC) was first dispersed in a suitable solvent and then the ionic form (Fe 3+ ) of iron precursors, such as (Fe 2( SO4)3*xH2O and allow it to react until the reaction is complete, thereby allowing the reaction to proceed thermally in the solvent phase.

[0111] The solvent used for the reaction is preferably selected from polar protic solvents such as ethanol, methanol and isopropanol.

[0112] The reaction is preferably carried out at a temperature above 40° C., more preferably above 60° C., even more preferably above 80° C. The reaction temperature is preferably below 200° C., more preferably below 180° C., even more preferably below 160° C.

[0113] The reaction is preferably carried out at least 10 minutes, more preferably at least 30 minutes, even more preferably at least 1 hour time period at the reflux temperature of the reaction mixture. The reaction time period is preferably less than 12 hours, more preferably less than 6 hours. Advantageously, the reaction time period scope is 2 to 4 hours.

[0114] The reaction product represented by the formula (II) of the present invention is separated by a conventional separation technique (filtration, centrifugation, etc.) and then dried at a temperature of 60°C to 100°C.

[0115] The method for preparing the vulcanizable elastomeric compound for tire according to the present invention will be described in detail below.

[0116] The method is characterized by one or more of the following preferred aspects alone or in combination with each other, in particular by using a compound represented by the following formula (II):

[0117] WF-O-ROS-GC-Fe (II)

[0118] wherein WF represents a white filler, O represents one or more oxygen bridges, ROS represents an organo-silane residue, GC represents one or more coordinating groups that form a chelate with the ionic form of iron, and Fe represents the ionic form (Fe 3+ ) of iron.

[0119] The process of the present invention may be a continuous process, but preferably, it is a discontinuous process (batch).

[0120] When discontinuous, the process of the invention can be carried out in one or more mixers, preferably in a single mixer.

[0121] The process according to the invention comprises a step of mixing (step 1 ) at least one diene elastomeric polymer and at least one additive for an elastomeric compound, said additive not being a vulcanizing agent.

[0122] The at least one additive for the elastomeric compound mixed with the at least one diene elastomeric polymer in the mixing step (1) may be, for example, a compound of formula (II) according to the invention, reinforcing fillers, antioxidants, waxes, plasticizers, etc.

[0123] Typically, in the mixing step (1), no vulcanizing agent is added, and preferably, not even a vulcanization accelerator or retarder is added.

[0124] In the process of the present invention, in the mixing step (1), the compound of the formula (II) of the present invention can be fed in whole or in part.

[0125] Preferably, all of the compounds of formula (II) according to the present invention are fed in step (1).

[0126] In step (1), mixing is performed at a mixing temperature of usually 70° C. to 160° C., and lasts for usually 2 to 20 minutes.

[0127] Before carrying out step (2), it may be advantageous to carry out a step of draining and / or remaining non-vulcanizable elastomeric compound, in order to allow any reaction to be completed.

[0128] Preferably, the rubber material of step (1) is discharged before performing step (2).

[0129] In the subsequent step (2), at least one vulcanizing agent is incorporated. Possibly, in step (2), at least one vulcanization accelerator, at least one vulcanization retarder and, if not already fully fed into the mixing step (1), the compound of formula (II) according to the invention may be added.

[0130] In step (2) of the process of the present invention, the mixing temperature is generally kept below 160° C., preferably 140° C., more preferably 120° C., in order to avoid any undesired pre-crosslinking phenomena.

[0131] Generally, in step (2), mixing may be performed at a mixing temperature of 70° C. to 155° C. for a period of 2 to 10 minutes.

[0132] At the end of step (2), the method of the invention involves a step of unloading the vulcanizable elastomeric compound destined for subsequent typical processing steps for the production of tyres and components thereof.

[0133] In one or more steps of the method of the present invention, other additives commonly used in the production of tire rubber compounds may be added, which additives are selected based on the specific application of the composition. For example, the following substances may be added: anti-aging agents, plasticizers, adhesives, antiozonants, modified resins or mixtures thereof.

[0134] In the process of the invention, the at least one diene elastomeric polymer may be chosen from those customarily used in sulfur-vulcanizable elastomeric compositions particularly suitable for the production of tyres, i.e. from elastomeric polymers or copolymers having unsaturated chains and having a glass transition temperature (Tg) generally below 20° C., preferably in the range from 0° C. to −110° C.

[0135] Preferably, the diene elastomeric polymer has a weight-average molecular weight (Mw) higher than 80 000 g / mol.

[0136] These polymers or copolymers may be of natural origin or may be obtained by solution polymerization, emulsion polymerization or gas phase polymerization of one or more conjugated dienes, optionally mixed with at least one comonomer chosen from monovinyl aromatics and / or polar comonomers in an amount not exceeding 60% by weight.

[0137] The conjugated diene generally contains 4 to 12, preferably 4 to 8 carbon atoms, and may be selected, for example, from 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, 1,3-hexadiene, 3-butyl-1,3-octadiene, 2-phenyl-1,3-butadiene, and mixtures thereof.

[0138] 1,3-Butadiene and isoprene are particularly preferred.

[0139] The monovinyl aromatic hydrocarbons which may optionally be used as comonomers generally contain 8 to 20, preferably 8 to 12 carbon atoms, and may be selected, for example, from: styrene; 1-vinylnaphthalene; 2-vinylnaphthalene; various alkyl, cycloalkyl, aryl, alkylaryl or arylalkyl derivatives of styrene, such as α-methylstyrene, 3-methylstyrene, 4-propylstyrene, 4-cyclohexylstyrene, 4-dodecylstyrene, 2-ethyl-4-benzylstyrene, 4-p-tolyl-styrene, 4-(4-phenylbutyl)styrene and mixtures thereof. Styrene is particularly preferred.

[0140] Polar comonomers which may be used optionally may be selected, for example, from vinylpyridine, vinylquinoline, acrylic acid and alkylacrylic acid esters, nitriles or mixtures thereof, such as methyl acrylate, ethyl acrylate, methyl methacrylate, ethyl methacrylate, acrylonitrile and mixtures thereof.

[0141] Preferably, the diene elastomeric polymer that can be used in the present invention can be chosen, for example, from cis-1,4-polyisoprene (natural or synthetic, preferably natural rubber), 3,4-polyisoprene, polybutadiene (especially polybutadiene with a high 1,4-cis content), isoprene / isobutylene copolymers, optionally halogenated, 1,3-butadiene / acrylonitrile copolymers, styrene / 1,3-butadiene copolymers, styrene / isoprene / 1,3-butadiene copolymers, styrene / 1,3-butadiene / acrylonitrile copolymers and mixtures thereof.

[0142] The above-mentioned vulcanizable elastomeric rubber compound may possibly contain an elastomeric polymer of one or more monoolefins and an olefin comonomer or a derivative thereof. The monoolefin may be selected from: ethylene and α-olefins generally containing 3 to 12 carbon atoms, such as propylene, 1-butene, 1-pentene, 1-hexene, 1-octene and mixtures thereof. The following are preferred: copolymers selected from ethylene and α-olefins, optionally with dienes; isobutylene homopolymers or copolymers thereof with a small amount of dienes, which are optionally at least partially halogenated. The dienes that may be present generally contain 4 to 20 carbon atoms, and are preferably selected from: 1,3-butadiene, isoprene, 1,4-hexadiene, 1,4-cyclohexadiene, 5-ethylidene-2-norbornene, 5-methylene-2-norbornene, vinyl norbornene and mixtures thereof. Among them, the following are particularly preferred: ethylene / propylene (EPR) copolymers or ethylene / propylene / diene (EPDM) copolymers; polyisobutylene; butyl rubber; halogenated butyl rubber, in particular chlorobutyl rubber or bromobutyl rubber; or mixtures thereof.

[0143] It is also possible to use diene elastomeric polymers or elastomeric polymers functionalized by reaction with suitable terminators or coupling agents. In particular, diene elastomeric polymers obtained by anionic polymerization in the presence of organometallic initiators, in particular organolithium initiators, can be functionalized by reacting the residual organometallic groups derived from the initiator with suitable terminators or coupling agents, such as imines, carbodiimides, alkyltin halides, substituted benzophenones, alkoxysilanes or aryloxysilanes.

[0144] In the process of the invention for preparing a vulcanizable elastomeric compound, said at least one elastomeric polymer may comprise, in the form of a mixture, one or more diene elastomeric polymers as defined above, which may advantageously be subjected to a mastication step (step 1-0) for better blending.

[0145] In the process of the invention, at least one elastomeric polymer or a mixture of two or more elastomeric polymers as defined above is used in an amount totaling 100 phr.

[0146] In the process of the present invention, at least one vulcanizing agent is preferably selected from sulfur, or sulfur-containing molecules (sulfur donors), such as caprolactam disulfide (CLD), bis(trialkoxysilyl)propyl] polysulfide, dithiophosphates, phosphoryl polysulfide (SDT) and mixtures thereof.

[0147] Preferably, the vulcanizing agent is sulfur, preferably selected from soluble sulfur (crystalline sulfur), insoluble sulfur (polymeric sulfur), (iii) oil-dispersed sulfur and mixtures thereof.

[0148] Commercial examples of suitable vulcanizing agents are 65% sulfur known under the trade name Rhenogran (Lanxess), 67% sulfur known under the trade name Crys tex OT33 (Eastman), 95% sulfur known under the trade name Solvay Schwefel KC, rhombic crystalline sulfur known under the trade name Sulfur (1% oil and 0.3% silica) (Zolfindustria).

[0149] The vulcanizing agents may be present in the vulcanizable elastomeric compound in a total amount generally ranging from 0.1 to 15 phr, preferably from 0.5 to 10 phr, even more preferably from 1 to 7 phr.

[0150] The elastomeric compound of the invention may comprise one or more vulcanizing agents as defined above, in the form of a mixture.

[0151] In the process of the present invention, the vulcanizing agent is preferably used together with auxiliary agents known to those skilled in the art, such as vulcanization accelerators and / or retarders.

[0152] In the process of the present invention, the vulcanization accelerator is preferably selected from dithiocarbamates, guanidines, thioureas, thiazoles, sulfenamides, sulfenyl imides, thiurams, amines, xanthates and mixtures thereof.

[0153] Preferably, the accelerator is selected from N-cyclohexyl-2-benzothiazole-sulfenamide (CBS), N-tert-butyl-2-benzothiazole-sulfenamide (TBBS) and mixtures thereof.

[0154] A commercial example of a suitable accelerator is N-cyclohexyl-2-benzothiazole-sulfenamide sold by Lanxess. (CBS or CZ).

[0155] The accelerators may be present in the vulcanizable elastomeric compound in a total amount generally ranging from 0.05 to 10 phr, preferably from 0.1 to 5 phr.

[0156] The elastomeric compound of the invention may comprise one or more accelerators as defined above in the form of a mixture.

[0157] In the process of the present invention, the vulcanization retarder may be selected from, for example, urea, phthalic anhydride, N-nitrosodiphenylamine, N-cyclohexylthiophthalimide (CTP or PVI) and mixtures thereof.

[0158] A commercial example of a suitable retarder is N-cyclohexylthiophthalimide VULKALENT G from Lanxess.

[0159] The delay agent may be present in the vulcanizable elastomeric compound in an amount generally ranging from 0.05 phr to 2 phr.

[0160] The elastomeric compound of the invention may comprise one or more retarders as defined above in the form of a mixture.

[0161] Preferably, in the process of the invention, preferably in the mixing step (1), one or more optional additives may be fed, such as at least one reinforcing filler, at least one antioxidant, at least one wax and at least one plasticizer.

[0162] In the process of the invention, the reinforcing filler is selected from carbon black, conventional silica, such as sand silica precipitated with strong acids, preferably amorphous, hydrotalcite, diatomaceous earth, calcium carbonate, titanium dioxide, talc, aluminum oxide, aluminosilicates, kaolin, silicate fibers and mixtures thereof.

[0163] Preferably, the additional reinforcing filler is selected from carbon black, conventional silica, silicate fibers and mixtures thereof, preferably it is silica.

[0164] Carbon black may be selected from those of standard grades for tires or having a surface area (measured according to ASTM D6556-16) of not less than 20 m 2 / g, more preferably greater than 50m 2 / g those.

[0165] A commercial example of a suitable reinforcing filler is Zeosil 1165MP silica from Solvay Rhodia.

[0166] Commercial examples of carbon black are N375 or N234 sold by the Birla Group (India) or Cabot Corporation.

[0167] The reinforcing fillers may be present in the vulcanizable elastomeric compound in an amount ranging generally from 0 phr to 120 phr, preferably from 3 phr to 80 phr.

[0168] In one embodiment, the reinforcing filler may be absent, in which case the reinforcing function is performed by the compound of formula (II) according to the invention.

[0169] For some applications, the elastomeric compound prepared according to the process of the invention may contain at least 1 phr, more preferably at least 2 phr, more preferably at least 3 or 4 phr of carbon black, which advantageously protects the elastomer from aging caused by the action of ultraviolet radiation.

[0170] The elastomeric compound of the invention may comprise one or more reinforcing fillers as defined above, in the form of a mixture.

[0171] In the process according to the invention, as antioxidants there may be used phenylenediamine, diphenylamine, dihydroquinoline, phenol, benzimidazole, hydroquinone and derivatives thereof, possibly in the form of mixtures.

[0172] In the method of the present invention, the antioxidant is preferably selected from N-isopropyl-N′-phenyl-p-phenylenediamine (IPPD), N-(1,3-dimethyl-butyl)-N′-phenyl-p-phenylenediamine (6PPD), N,N′-bis-(1,4-dimethyl-pentyl)-p-phenylenediamine (77PD), N,N′-bis-(1-ethyl-3-methyl-pentyl)-p-phenylenediamine (DOPD), N,N′-bis-(1,4-dimethyl-pentyl)-p-phenylenediamine, N,N′-diphenyl-p-phenylenediamine diamine (DPPD), N,N′-xylene-p-phenylenediamine (DTPD), N,N′-bis-β-naphthyl-p-phenylenediamine (DNPD), N,N′-bis(1-methylheptyl)-p-phenylenediamine, N,N′-di-sec-butyl-p-phenylenediamine (44PD), N-phenyl-N-cyclohexyl-p-phenylenediamine, N-phenyl-N′-1-methylheptyl-p-phenylenediamine, and the like and mixtures thereof, preferably N-(1,3-dimethyl-butyl)-N′-phenyl-p-phenylenediamine (6PPD).

[0173] A commercial example of a suitable antioxidant is 6PPD from Solutia / Eastman.

[0174] Antioxidants may be present in the vulcanizable elastomeric compound in a total amount ranging generally from 0 phr to 20 phr, preferably from 0.5 phr to 10 phr.

[0175] In the process of the present invention, the wax may be, for example, a petroleum wax or a mixture of paraffin waxes.

[0176] Commercial examples of suitable waxes are Repsol n-paraffin mixtures from Rhein Chemie and 654 microcrystalline wax.

[0177] The wax may be present in the vulcanizable elastomeric compound in a total amount ranging generally from 0 to 20 phr, preferably from 0.5 to 5 phr.

[0178] In the process of the present invention, in order to further improve the processability, the elastomeric rubber can be mixed with at least one plasticizer, which is generally selected from mineral oils, vegetable oils, synthetic oils, polymers with low molecular weight and mixtures thereof, such as aromatic oils, naphthenic oils, phthalates, soybean oil and mixtures thereof. The amount of plasticizer generally ranges from 0 phr to 70 phr, preferably from 5 phr to 30 phr. Preferably, the plasticizer is added during the chewing step of the polymer, if present.

[0179] A fourth aspect of the invention is represented by a vulcanizable elastomeric compound obtainable by the process according to the third aspect of the invention.

[0180] In the elastomeric compound according to the invention, iron is present in ionic form as Fe 3+ It is bound by a coordinate bond to form the compound represented by the formula (II) of the present invention, but is not in the form of metallic iron (Fe°).

[0181] The amount of iron in the compounds can be determined, for example, by ICP-AES (Inductively Coupled Plasma - Atomic Emission Spectroscopy) spectroscopy, as described in the experimental part.

[0182] The vulcanizable elastomeric compound of the present invention may be incorporated into one or more components of a tire.

[0183] By means of the process of the present invention, it is possible to eliminate zinc incorporated into rubber compounds, with important benefits for the environment, without deteriorating or even improving their properties compared to comparable conventional rubber compounds.

[0184] According to a fifth aspect of the invention, the elastomeric rubber compound of the present invention is applied to tire components such as tread, base layer, wear-resistant elongated elements, sidewalls, sidewall inserts, micro sidewalls, underlays, rubber layers, filler strips and sheets, more preferably to the tread, base layer and sidewalls and underlays.

[0185] Preferably, the tire component according to the invention consists of a vulcanizable compound according to the invention (green component) or of a vulcanized compound obtained by vulcanization thereof (vulcanized component).

[0186] A sixth aspect of the present invention is a tire for a vehicle wheel, comprising at least one of the above-mentioned components.

[0187] Preferably, the tire for vehicle wheels of the present invention comprises at least one tire component consisting of a vulcanizable elastomeric compound (green component) according to the second aspect of the present invention or of a vulcanized elastomeric compound obtained by vulcanization thereof.

[0188] In one embodiment, a tire for a vehicle according to the present invention comprises at least:

[0189] - a carcass structure comprising at least a carcass ply having opposite lateral edges associated with respective bead structures;

[0190] - a possible pair of side walls respectively applied to the lateral surfaces of the carcass structure in an axially external position;

[0191] - a possible belt structure applied in a radially external position with respect to the carcass structure;

[0192] - a crown applied in a radially external position to said carcass structure or to the belt structure, if present,

[0193] - a possible layer of elastomeric material, called sublayer, applied in a radially internal position relative to said crown,

[0194] At least one component selected from the pair of sidewalls, the base layer and the crown comprises an elastomeric compound according to the invention, or preferably consists of an elastomeric compound according to the invention.

[0195] An embodiment according to the invention relates to tires for high performance vehicles (HP, SUV and UHP), wherein at least one component preferably selected from the base layer, the sidewalls and the crown comprises or preferably consists of an elastomeric compound according to the invention.

[0196] An embodiment according to the invention relates to a tyre for heavy vehicles, wherein at least one component, preferably selected from the base layer, the sidewall and the crown, comprises or preferably consists of an elastomeric compound according to the invention.

[0197] The tyre according to the invention may be a tyre for a two-wheeled, three-wheeled or four-wheeled vehicle.

[0198] In one embodiment, the tyre according to the invention is a tyre for bicycle wheels.

[0199] A tyre for a bicycle wheel usually comprises a carcass structure rotating around a pair of bead cores at the beads and a crown arranged in a radially outer position with respect to the carcass structure.

[0200] The carcass structure is designed to withstand the inflation pressure and support the weight of the bicycle and the cyclist. It comprises one or more carcass plies, each of which comprises a plurality of appropriately oriented reinforcing cords. In case of multiple carcass plies, they are inclined relative to each other to form a cross structure.

[0201] The task of the bead core is to ensure that the tire is anchored to the rim.

[0202] In a radially inner position of the carcass structure, an air chamber may be provided, into which pressurized air is introduced.

[0203] The tire according to the invention can be used for summer or winter use or for all seasons.

[0204] The tire according to the present invention can be manufactured according to a method comprising:

[0205] - Building components of a green tyre on at least one forming drum;

[0206] - Shaping, molding and vulcanizing tires;

[0207] Wherein at least one of the components for constructing a green tire comprises:

[0208] - Production of at least one green component comprising or preferably consisting of the vulcanizable elastomeric compound according to the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0209] Figure 1 A radial half-section of a tire for a vehicle wheel according to the invention is shown.

[0210] Figure 2 The Cartesian graphs associated with the vulcanization curves of the elastomeric compounds RIF1, CON1 and INV1 described in Example 2 are shown.

[0211] Figure 3 The method for synthesizing SiO2-APTES is shown. x -Fe Y Nominal molar ratio of the material (n Fe(前体) / n APTES ) and in SiO2-APTES x -Fe Y The actual molar ratio (n Fe / n APTES ). The black dashed line shows the ideal situation that would exist if the two ratios were consistent.

[0212] In particular, Figure 1 Shown is a radial half-section of a tyre for vehicle wheels comprising a vulcanized elastomeric compound prepared by vulcanizing an elastomeric compound prepared according to the method of the invention.

[0213] exist Figure 1 In the figure, "a" represents the axial direction, "X" represents the radial direction, and in particular, XX represents the profile of the equatorial plane. Figure 1 Only a portion of the tire is shown, the remaining portion not shown being identical and arranged symmetrically with respect to the equatorial plane "XX".

[0214] The tyre 100 for a four-wheeled vehicle comprises at least one carcass structure including at least one carcass layer 101 having respectively opposite end flaps engaged with corresponding annular anchoring structures 102, called bead cores, possibly associated with filler strips 104.

[0215] The carcass layer 101 is optionally made of an elastomeric compound.

[0216] The tire region including the bead core 102 and the filler bead 104 forms a bead structure 103 for anchoring the tire to a corresponding mounting rim (not shown).

[0217] The carcass structure is usually of radial type, i.e. the reinforcing elements of at least one carcass layer 101 are located in a plane comprising the axis of rotation of the tire and substantially perpendicular to the equatorial plane of the tire. The reinforcing elements are usually composed of textile cords, such as rayon, nylon, polyester (such as polyethylene naphthalate, PEN). The carcass structure is formed by folding the opposite lateral edges of at least one carcass layer 101 back around an annular anchoring structure 102 so as to form a tyre. Figure 1 A so-called carcass wing 101a is shown associating each bead structure with the carcass structure.

[0218] In one embodiment, the connection between the carcass structure and the bead structure may be provided by a second carcass layer ( Figure 1 ), which second carcass layer is applied in an axially outer position relative to the first carcass layer.

[0219] A wear strip 105 , optionally made of an elastomeric compound, is arranged in an outer position of each bead structure 103 .

[0220] The carcass structure is associated with a belt structure 106 comprising one or more belt layers 106a, 106b placed radially superimposed relative to each other and relative to the carcass layer, the one or more belt layers 106a, 106b typically having textile and / or metal reinforcing cords incorporated in a layer of vulcanized elastomeric compound.

[0221] Such reinforcing cords may have a cross orientation relative to the circumferential development direction of the tire 100. A "circumferential" direction is a direction generally facing the direction of rotation of the tire.

[0222] At least one zero degree reinforcement layer 106c, commonly referred to as a "0° belt", can be applied to the belt layers 106a, 106b in a radially outermost position, which typically comprises a plurality of elongated reinforcing elements, typically metal or textile cords, oriented in a substantially circumferential direction so as to form an angle of several degrees (e.g., an angle of about 0° to 6°) relative to a direction parallel to the equatorial plane of the tire, and coated with a vulcanized elastomeric compound.

[0223] A crown 109 of vulcanized elastomeric compound is applied in a radially external position to the belt structure 106 .

[0224] Furthermore, respective sidewalls 108 of vulcanized elastomeric compound are applied in an axially outer position on the lateral surface of the carcass structure, each sidewall 108 extending from one of the lateral edges of the tread 109 at a respective bead structure 103 .

[0225] In the radially outer position, the crown 109 has a rolling surface 109a intended to come into contact with the ground. Figure 1109a) are connected to define a plurality of blocks having various shapes and sizes distributed on the rolling surface 109a) and are usually made on the surface 109a. For simplicity, the surface is Figure 1 Indicated as smooth.

[0226] A bottom layer 111 of vulcanized elastomeric compound may be arranged between the belt structure 106 and the tread crown 109 .

[0227] It is possible to optionally provide, in the connection zone between the sidewall 108 and the crown 109, a strip consisting of an elastomeric compound 110 (generally called a “mini-sidewall” of vulcanized elastomeric compound), generally obtained by coextrusion with the crown 109 and allowing to improve the mechanical interaction between the crown 109 and the sidewall 108. Preferably, the ends of the sidewall 108 directly overlap the lateral edges of the crown 109.

[0228] In the case of a tubeless tyre, a rubber layer 112 , generally called “liner”, may also be provided in a radially internal position relative to the carcass layer 101 , this rubber layer 112 providing the necessary impermeability to the inflation of the tyre.

[0229] The rigidity of the tire sidewall 108 may be improved by providing the bead structure 103 with a reinforcement layer 120 commonly referred to as an "outer fender" or an additional belt-like insert.

[0230] The outer fender 120 is a reinforcement layer that is wound around the corresponding bead core 102 and the filler strip 104 to at least partially surround them, and the reinforcement layer is arranged between at least one carcass layer 101 and the bead structure 103. Generally, the outer fender is in contact with the at least one carcass layer 101 and the bead structure 103.

[0231] The outer retainer 120 generally comprises a plurality of textile cords incorporated within a layer of vulcanized elastomeric compound.

[0232] The bead structure 103 of the tyre may comprise an additional protective layer, generally referred to by the term “chafer” 121 or protective strip, and having the function of increasing the rigidity and integrity of the bead structure 103 .

[0233] The chafer 121 generally includes a plurality of cords incorporated in a rubber layer of a vulcanized elastomeric compound. Such cords are generally made of textile materials (such as aramid or rayon) or metal materials (such as steel cords).

[0234] The layer or sheet of elastomeric compound may be arranged between the belt structure and the carcass structure. The layer may have a uniform thickness. Alternatively, the layer may have a variable thickness in the axial direction. For example, relative to the center (crown) zone, the layer may have a greater thickness near its axial outer edge.

[0235] Advantageously, the layer or sheet may extend over a surface substantially corresponding to the surface over which said belt structure extends.

[0236] In a preferred embodiment, a layer or sheet of elastomeric compound as described above may be placed between said belt structure and said crown, said additional layer or sheet preferably extending over a surface substantially corresponding to the surface of extension of said belt structure.

[0237] The elastomeric compound according to the invention may advantageously be incorporated into one or more tire components selected from the group consisting of belt structure, carcass structure, tread, baselayer, sidewalls, mini-sidewalls, sidewall inserts, beads, outer bead wrappers, bead wrappers, sheets and wear strips, preferably at least into the sidewalls and / or baselayer.

[0238] According to an embodiment not shown, the tyre may be a tyre for motorcycle wheels, which is generally a tyre having a rectilinear portion characterized by a high tread camber.

[0239] According to an embodiment not shown, the tyre may be a tyre for a bicycle wheel.

[0240] According to an embodiment not shown, the tire can be a tire for a heavy transport vehicle wheel, such as a truck, bus, trailer, van, and generally for vehicles where the tire is subjected to high loads. Preferably, such a tire is suitable for mounting on a rim having a diameter equal to or greater than 17.5 inches for a directional wheel or trailer wheel.

[0241] The description of some preparation examples and comparative examples according to the present invention is only for illustration but not to limit the scope of the present invention, as described below.

[0242] Experimental Section

[0243] Analytical methods

[0244] White filler functionalization

[0245] The functionalization of the white filler was verified by ATR-FTIR, TGA, CHNS and BET analysis.

[0246] ATR-FTIR analysis The analysis was performed using a Perkin Elmer Spectrum 100 instrument (using a resolution of 4 cm -1 Spectrum, 650 to 400 cm -1area, 32 scans).

[0247] Thermogravimetric analysis (TGA) With a constant air flow rate (50 mL min -1 ) was performed on a TGA / DCS1 STARe system (Mettler Toledo). The method used involved applying a 10°C min -1 A heating ramp was performed starting from an initial temperature of 30°C until a final temperature of 1000°C. Two 15 min isotherms were also added at 150°C and 1000°C. The measurements were performed in an alumina crucible with a volume of 75 μL.

[0248] CHNS analysis The analysis was performed with an Elementar VarioMICRO analyzer in CHNS configuration. The uncertainty of the measurement was declared to be 0.1%. The measured values ​​were normalized to the sulfonamide standard. The combustion tower was at a temperature of 1150°C, while the reduction tower was at 850°C.

[0249] BET Analysis The porosity and surface area analysis was performed using a Micromeritics Tristar II porosity and surface area analysis instrument.

[0250] Determination of iron content

[0251] The iron content can be measured by ICP-AES spectroscopy (Inductively Coupled Plasma - Atomic Emission Spectroscopy) using an ICP synchronous plasma spectrometer (TJA IRIS II model; excitation source: radio frequency generator with a frequency of 27.12 MHz and a variable output power up to 1750 W).

[0252] MDR Rheological Analysis (According to ISO 6502): Using Alpha Technologies MDR2000 rheometer. Tested at 170°C with an oscillation frequency of 1.66 Hz (100 oscillations / minute) and an oscillation amplitude of ±0.5° for 10 minutes, measuring the time required to achieve an increase of two rheological units (TS2), the maximum torque value (MH), and the time required to achieve 30% (T30) and 100% (T100) of the maximum torque value (MH), respectively.

[0253] Properties of vulcanized materials

[0254] The elastomeric materials prepared in the aforementioned examples were vulcanized to obtain samples, on which analytical characterization and evaluation of dynamic mechanical properties were performed.

[0255] Unless otherwise stated, vulcanization was carried out in a mold in a hydraulic press at 170° C. and a pressure of 200 bar for about 10 minutes.

[0256] Static modulus : The static mechanical properties are measured at 23° C. according to ISO 37:2005 standard. In particular, the tensile stress at various elongation levels (10%, 50%, 100% and 300%, named in the order CA0.1, CA0.5, CA1 and CA3) is measured on samples of the vulcanized elastomeric composition.

[0257] Dynamic modulus Dynamic mechanical properties were measured using the following method in compression and tension operations using an Instron dynamic device. Vulcanized elastic cylindrical composite samples (length = 25 mm; diameter = 18 mm) were preloaded under compression to a longitudinal deformation of 25% relative to the initial length and were maintained at a predetermined temperature (10° C., 23° C. or 100° C.) during the test, subjecting them to a dynamic sinusoidal stress with an amplitude of ±3.5% relative to the preloaded length at frequencies of 1 Hz, 10 Hz and 100 Hz.

[0258] The dynamic mechanical properties are expressed in terms of dynamic elastic modulus (E′), viscous dynamic modulus (E″) and Tan δ (loss factor). The Tan δ value is calculated as the ratio between the viscous dynamic modulus (E″) and the dynamic elastic modulus (E′).

[0259] G (shear) dynamic modulus : They are measured using a Monsanto RPA Rheometer 2000 according to the following method: a cylindrical specimen with a weight range of 4.5 to 5.5 g is obtained by punching a sample of a vulcanizable elastomeric composition and vulcanizing it in the instrument "RPA" (at 170°C for 10 minutes). Dynamic measurements of the elastic shear modulus (G') of the vulcanized sample are carried out at 70°C, a frequency of 10 Hz, and strains of 0.1% and 10%. The dynamic elastic properties are expressed as the shear elastic dynamic modulus (G'), the shear viscosity dynamic modulus (G") and Tanδ (loss factor) at 3% and 9% strain. The Tanδ value is calculated as the ratio between the shear viscosity dynamic modulus (G") and the shear elastic dynamic modulus (E').

[0260] Example 1 - Preparation of functionalized silica

[0261] Materials used

[0262] Rhodia Zeosil MP1165 precipitated silica (surface area BET 160 m 2 / g)

[0263] Coupling agent (APTES): (3-aminopropyl)triethoxysilane H2N(CH2)3Si(OC2H5)3 (99%) produced by Sigma Aldrich;

[0264] Ferrous sulfate (Fe2(SO4)3*xH2O) produced by Sigma Aldrich;

[0265] Toluene produced by Alfa Aesar (99%);

[0266] - Anhydrous ethanol EtOH (99.9%) produced by Scharlau.

[0267] The preparation consists of a two-step process in which the silica is first functionalized with a coupling agent and, after recovery, the anhydrous powder is reacted with an iron precursor (hydrated ferric sulfate) to bind the ionic form (Fe) by forming a chelate with the coordinating group GC. 3+ ) of iron.

[0268] first step

[0269] In a 50 mL flask, 1 g of SiO2 powder was dispersed in 25 ml of toluene at 120°C with stirring for 10 minutes. Then, 0.394 ml of (3-aminopropyl) triethoxysilane (APTES) was added to the dispersion, calculated so that the molar ratio between APTES and the number of hydroxyl groups on the surface of silica was equal to 1:2, and the reaction was kept at 120°C with stirring for 24 hours (reflux condition). After cooling, the reaction product (SiO2-APTES) was recovered by vacuum filtration, washed twice with fresh toluene, and dried overnight in an oven at 80°C.

[0270] The above-described preparation of the functionalized silica (SiO2-APTES) obtained in the first step and the characterization by ATR-FTIR, TGA and CHNS analysis are similar to those described in WO 2020 / 110023 in the name of the present applicant and in "Design of a Zn Single-Site Curing Activator for a More Sustainable Sulfur Cross-Link Formation in Rubber" Ind. Eng. Chem. Res. 2021, 60, 101 80-10192 by S. Mostoni et al.

[0271] TGA and CHNS analysis allowed confirmation of the functionalization of the silica after reaction with APTES, the results being summarized in Table A below.

[0272] Table A

[0273]

[0274] Step 2

[0275] 1 g of the functionalized silica (SiO2-APTES) obtained in the first step was dispersed in 50 mL of ethanol at 100°C for 20 minutes under stirring to obtain a uniform suspension. A sufficient amount of iron precursor (Fe2(SO4)3*xH2O) was then added. Considering the molar ratio Fe / APTES (n Fe(前体) / n APTES ) equal to 1:20, 1:10, 1:2, 1:1 and 2:1, assuming that iron ions cannot directly bind to the surface of silica nanoparticles, the amount of iron precursor used was calculated.

[0276] The reaction was carried out for 2 hours, and after cooling, the reaction product (SiO2-APTES-Fe) was isolated by vacuum filtration and washed twice with fresh ethanol to remove unreacted salts and dried at 80°C for 12 hours.

[0277] In this way, SiO2-APTES was prepared. x -Fe Y The five different catalysts are shown in Figure 2, where the indices Y and X refer to the nominal molar ratios of Fe / APTES (n Fe(前体) / n APTES ).

[0278] Characterization of the obtained materials

[0279] ICP-OES - Inductively Coupled Plasma Optical Emission Spectrometry

[0280] This characterization technique allows the determination of Fe anchored to silica nanoparticles via amine ligands (APTES). 3+ ion amount, and allows to estimate the type of metal-ligand coordination by analyzing materials prepared with different iron starting from different contents of metal precursors.

[0281] ICP analysis was performed using a Perkin Elmer Optima 7000DV spectrometer (WinLab32 software control) coupled to a microwave decomposition system. For each analysis, the sample was prepared by finely grinding 0.2 g of powdered material and then dissolving it in an acid solution consisting of 4 mL of HNO3, 3 mL of HCl and 1 mL of HF. The sample was then treated in the decomposition system with the following steps: i) 8 minutes, 160°C, ii) 5 minutes, 200°C, iii) 20 minutes, 200°C. The solution was diluted with 12 mL of milliQ water, and finally 15 mL of the solution was further diluted 1:100 and introduced into the ICP instrument for analysis. The evaporated sample was transported to the plasma source by a constant argon flow of 20 L / min.

[0282] Table B below shows the Fe determined by ICP and TGA measurements for each of the five prepared catalysts. 3+ The number of ions and APTES molecules.

[0283] Table B

[0284]

[0285] Fe coordinated by APTES molecules 3+ The amount of ions increases with the amount of metal precursor used during the synthesis. However, even in the presence of excess iron in SiO2-APTES x -Fe Y The highest n obtained in the material Fe / n APTES The molar ratio is always about 1, and it goes up to n Fe / n APTES =0.5, calculated molar ratio (n Fe / n APTES ) and nominal molar ratio (n Fe(前体) / n APTES ) is almost the same ( Figure 3 ). This trend shows that in SiO2-APTES x -Fe Y In the present study, the iron metal center is preferentially coordinated by the silica-anchored APTES molecules, even though bidorbination cannot be excluded when the amount of iron used during the synthesis is insufficient compared to the amount of APTES.

[0286] TEM-Transmission electron microscopy analysis

[0287] The morphology of the activators was studied by means of TEM and TEM-EDX analysis, the latter notably allowing the elemental composition of the material to be studied.

[0288] Using a Gatan Rio TM The analysis was performed using a Jeol Jem-2100plus TEM transmission electron microscope with a complementary metal oxide semiconductor (CMOS) camera and 8 megapixels. The powder samples to be analyzed were loaded on a specific copper grid for TEM analysis.

[0289] According to the analysis carried out, it is observed that the iron is distributed substantially uniformly on the surface of the silica particles and that sulfide ions are present, which may be derived from residual sulfate groups of the metal precursors, which probably remain within the coordination sphere of the metal but do not affect its reactivity.

[0290] Example 2

[0291] Preparation of elastomeric compounds

[0292] Table 1 below shows the formulations of a reference compound comprising silica and zinc oxide (RIF1), a comparative compound comprising silica and iron sulfate itself (CON1), and a compound according to the invention (INV1), wherein the compound according to the invention comprises a vulcanization activator SiO2-APTES2-Fe1 with a Fe / APTES molar ratio of 1:2 prepared as described in Example 1.

[0293] The reference compound (RIF1) is a conventional compound commonly used in the production of tire components, and the comparative compound (CON1) is a compound prepared to demonstrate the inactivity of common iron salts relative to the vulcanization activator used in the inventive compound (INV1).

[0294] Table 1

[0295] Components RIF1 CON1 INV1 IR 100 100 100 Silicon dioxide 48.0 48.0 2.2 Silane 3.84 3.84 0.18 6PPD 2 2 2 Stearic acid 2 2 - ZnO 1.85 - - Ferrous Sulfate - 10.66 - <![CDATA[SiO2-APTES2-Fe1]]> - - 50.87 CBS 1.6 1.6 1.6 Sulfur (67%) 3 3 3

[0296] IR: high cis synthetic polyisoprene (minimum 96%), obtained by polymerization in solution with Ziegler / Natta catalysts; supplier NIZHNEKAMSKNEFTECHIM EXPORT;

[0297] Silica: Zeosil 1115MP (surface area BET 95-120m 2 / g, white microspheres obtained by precipitation from sodium silicate solution with sulfuric acid. It does not contain crystalline silica. Supplier SOLVAY RHODIA OPERATIONS

[0298] Silane: TESPD bis-(3-triethoxy-silyl-propyl) disulfide, supplier Jingzhou Jianghan Fine Chemicals

[0299] 6PPD: N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine, Supplier: SOLUTIA / EASTMAN

[0300] Stearic acid: Supplier TEMIX OLEO SRL

[0301] ZnO(80): 80% zinc oxide, 20% polymer binder and dispersant, supplier LANXESS ADD

[0302] Ferrous sulfate: Fe2(SO4)3*xH2O produced by Sigma Aldrich

[0303] CBS: N-cyclohexyl-2-benzothiazolesulfenamide, cyclohexylamine content <1%, DUSLO supplier

[0304] Sulfur: Crystex OT33 amorphous sulfur, insoluble in CS2 and toluene. Treated with 33% hydrotreated heavy naphthenic distillate (petroleum) (supplier EASTMAN).

[0305] All components except sulfur and accelerator (CBS) were mixed together in an internal mixer (model Pomini PL 1.6) for about 5 minutes (first step). Once the temperature reached 145 ± 5 ° C, the elastomeric compound was unloaded. Then sulfur and accelerator (CBS) were added in an open mill and mixed (second step).

[0306] Using the compounds of Table 1, samples were prepared on which MDR rheological measurements and (shear) dynamic modulus G were performed as described above.

[0307] The results are summarized in Table 2 below.

[0308] Table 2

[0309]

[0310]

[0311] The results show that the rubber compound (INV1) of the present invention containing the vulcanization activator SiO2-APTES2-Fe1 of the present invention is not only different from the rubber compound containing ordinary Fe 3+ The vulcanization efficiency is high compared to the comparative compound (CON1) containing salt, and relative to the reference compound containing a conventional zinc-based vulcanization activator.

[0312] High G'(3%) and G'(9%) values ​​indicate high elasticity of the rubber compound, predicting high tire response and therefore better performance during its use. Conversely, low values ​​of Tan δ(3%) and Tan δ(9%) indicate low hysteresis and therefore low rolling resistance values ​​of the tire.

[0313] Fe2(SO4)3 alone (ie without forming a metal complex with organic ligands anchored on the silica surface) is not able to activate the sulfurization process, since low torque values ​​and thus poor mechanical properties are obtained.

[0314] The results obtained confirm that the sulfurization activator SiO2-APTES2-Fe1 has a decisive influence on the sulfurization efficiency, leading to the development of heterogeneous catalysts acting as bifunctional fillers, whose chemistry can tune the final properties of the material.

[0315] Figure 2 Shown are Cartesian graphs relating to the vulcanization curves of elastomeric compounds RIF1, CON1 and INV1.

[0316] By using the compounds of the invention as vulcanization activators, a complete and homogeneous dispersion of iron is obtained, with undoubted advantages in the subsequent vulcanization reaction. Furthermore, the lack of zinc makes these compounds sustainable from an environmental point of view, thus avoiding the release of zinc into the environment, which is toxic to aquatic life.

[0317] Example 3

[0318] Preparation of elastomeric compounds

[0319] Table 3 below shows the formulations of reference compounds containing silica and variable amounts of zinc oxide (RIF2 and RIF3) and a compound according to the invention (INV2) containing a vulcanization activator SiO2-APTES2-Fe1 with a Fe / APTES molar ratio of 1:2 prepared as described in Example 1, and no vulcanization accelerator (CBS).

[0320] Table 3

[0321]

[0322]

[0323] IR: High cis synthetic polyisoprene (minimum 96%), obtained by polymerization in solution with Ziegler / Natta catalysts; supplier NIZHNEKAMSKNEFTECHIM EXPORT

[0324] Silica: Zeosil 1115MP (surface area BET 95-120m 2 / g, white microspheres obtained by precipitation from sodium silicate solution with sulfuric acid. It does not contain crystalline silica. Supplier SOLVAY RHODIA OPERATIONS

[0325] Silane: TESPD bis-(3-triethoxy-silyl-propyl) disulfide, supplier Jingzhou Jianghan Fine Chemicals

[0326] TMQ: polymeric 2,2,4-trimethyl-1,2-dihydroquinoline, trade name Vulkanox HS / LG, available from Lanxess.

[0327] 6PPD: N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine, Supplier: SOLUTIA / EASTMAN

[0328] Stearic acid: Supplier TEMIX OLEO SRL

[0329] ZnO(80): 80% zinc oxide, 20% polymer binder and dispersant, supplier LANXESS ADD

[0330] CBS: N-cyclohexyl-2-benzothiazolesulfenamide, cyclohexylamine content <1%, DUSLO supplier

[0331] PVI: N-cyclohexylthiophthalimide, supplier: Solutia

[0332] Sulfur: Crystex OT33 amorphous sulfur, insoluble in CS2 and toluene. Treated with 33% hydrotreated heavy naphthenic distillate (petroleum) (supplier EASTMAN).

[0333] All components except sulfur and accelerator (CBS) are mixed together in an internal mixer (model Pomini PL 1.6) for about 5 minutes (first step). Once the temperature reaches 145 ± 5 ° C, the elastomeric compound is unloaded. Then sulfur and accelerator (CBS), if considered, are added in an open mill and mixed (second step).

[0334] Using the compounds of Table 3, samples were prepared on which MDR rheological measurements and static moduli CA0.1, CA0.5 and CA1 were performed as described above.

[0335] The results are summarized in Table 4 below.

[0336] Table 4

[0337]

[0338] The maximum torque results (MH) demonstrate the superior vulcanization efficiency of the inventive compound (INV2) containing the inventive vulcanization activator SiO2-APTES2-Fe1, even in the absence of an accelerator, compared to reference compounds (RIF2 and RIF3) containing different amounts of conventional zinc-based vulcanization activators.

[0339] The compound of the invention (INV2) shows higher Ca0.1, Ca0.5, Ca1 values ​​than the reference compounds (RIF2 and RIF3), indicating good elasticity of the compound and predicting good response characteristics and handling of the tire under service conditions, as well as greater durability of the tire.

[0340] Example 4

[0341] Preparation of elastomeric compounds

[0342] Table 5 below shows the formulations of reference compounds (RIF4 and RIF5) containing silica and variable amounts of zinc oxide and a compound according to the invention (INV3), the compound of the invention comprising a vulcanization activator SiO2-APTES2-Fe1 with a Fe / APTES molar ratio of 1:2 prepared as described in Example 1.

[0343] In this test, all compounds contained no vulcanization accelerator (CBS).

[0344] Table 5

[0345]

[0346]

[0347] IR: high cis synthetic polyisoprene (minimum 96%), obtained by polymerization in solution with Ziegler / Natta catalysts; supplier NIZHNEKAMSKNEFTECHIM EXPORT;

[0348] Silica: Zeosil 1115MP (surface area BET 95-120m 2 / g, white microspheres obtained by precipitation from sodium silicate solution with sulfuric acid. It does not contain crystalline silica. Supplier SOLVAY RHODIA OPERATIONS

[0349] Silane: TESPD bis-(3-triethoxy-silyl-propyl) disulfide, supplier Jingzhou Jianghan Fine Chemicals

[0350] TMQ: polymeric 2,2,4-trimethyl-1,2-dihydroquinoline, trade name Vulkanox HS / LG, available from Lanxess.

[0351] 6PPD: N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine, Supplier: SOLUTIA / EASTMAN

[0352] Stearic acid: Supplier TEMIX OLEO SRL

[0353] ZnO(80): 80% zinc oxide, 20% polymer binder and dispersant, supplier LANXESS ADD

[0354] PVI: N-cyclohexylthiophthalimide, supplier: Solutia

[0355] Sulfur: Crystex OT33 amorphous sulfur, insoluble in CS2 and toluene. Treated with 33% hydrotreated heavy naphthenic distillate (petroleum) (supplier EASTMAN).

[0356] All components except sulfur were mixed together in an internal mixer (model Pomini PL 1.6) for about 5 minutes (first step). Once the temperature reached 145 ± 5 ° C, the elastomeric compound was unloaded. The sulfur was then added in an open mill and mixing was carried out (second step).

[0357] Using the compounds of Table 5, samples were prepared on which MDR rheological measurements and static modulus CA0.1, Ca0.5, CA1 and CA3 were performed as described above.

[0358] The results are summarized in Table 6 below.

[0359] Table 6

[0360]

[0361] The values ​​of the maximum torque (MH) and the static modulus (Ca0.1, Ca0.5, Ca1 and Ca3) of the inventive rubber compound (INV3) show a significant increase in the vulcanization characteristic values ​​and how the inventive vulcanization activator SiO2-APTES2-Fe1 plays a crucial role both in the mechanical properties and in the vulcanization kinetics, as evidenced by the values ​​of TS2 and T30.

[0362] The data in Table 6 demonstrate that SiO2-APTES2-Fe1 is a complete and effective vulcanization activator, even in the absence of a vulcanization accelerator.

[0363] Example 5

[0364] Preparation of elastomeric compounds

[0365] Table 7 below shows the formulations of reference compounds containing silica and zinc oxide (RIF6 and RIF7) and a compound according to the invention (INV4) comprising a vulcanization activator SiO2-APTES2-Fe1 with a Fe / APTES molar ratio of 1:2 prepared as described in Example 1, and no vulcanization accelerator (CBS).

[0366] Table 7

[0367]

[0368]

[0369] IR: high cis synthetic polyisoprene (minimum 96%), obtained by polymerization in solution with Ziegler / Natta catalysts; supplier NIZHNEKAMSKNEFTECHIM EXPORT;

[0370] SBR: Styrene-butadiene copolymer with 23.5% styrene obtained in emulsion, trade name KER1500, from Synthos polymer.

[0371] Silica: Zeosil 1115MP (surface area BET 95-120m 2 / g, white microspheres obtained by precipitation from sodium silicate solution with sulfuric acid. It does not contain crystalline silica. Supplier SOLVAY RHODIA OPERATIONS

[0372] Silane: TESPD bis-(3-triethoxy-silyl-propyl) disulfide, supplier Jingzhou Jianghan Fine Chemicals

[0373] TMQ: polymeric 2,2,4-trimethyl-1,2-dihydroquinoline, trade name Vulkanox HS / LG, available from Lanxess.

[0374] 6PPD: N-(1,3-dimethylbutyl)-N′-phenyl-p-phenylenediamine, Supplier: SOLUTIA / EASTMAN

[0375] Stearic acid: Supplier TEMIX OLEO SRL

[0376] ZnO(80): 80% zinc oxide, 20% polymer binder and dispersant, supplier LANXESS ADD

[0377] CBS: N-cyclohexyl-2-benzothiazolesulfenamide, cyclohexylamine content <1%, DUSLO supplier

[0378] PVI: N-cyclohexylthiophthalimide, supplier: Solutia

[0379] Sulfur: Crystex OT33 amorphous sulfur, insoluble in CS2 and toluene. Treated with 33% hydrotreated heavy naphthenic distillate (petroleum) (supplier EASTMAN).

[0380] All components except sulfur and accelerator (CBS) are mixed together in an internal mixer (model Pomini PL 1.6) for about 5 minutes (first step). Once the temperature reaches 145 ± 5 ° C, the elastomeric compound is unloaded. Then sulfur and accelerator (CBS), if considered, are added in an open mill and mixed (second step).

[0381] Using the compounds of Table 7, samples were prepared on which MDR rheological measurements, (shear) dynamic modulus G and static modulus CA0.1 were performed as described above.

[0382] The results are summarized in Table 8 below.

[0383] Table 8

[0384]

[0385] The results in Table 8 show that the vulcanization activator SiO2-APTES2-Fe1 of the present invention exhibits high vulcanization efficiency even in compounds containing different polymers and in the absence of accelerators.

[0386] The vulcanization indicator values ​​Ca0.1, G′ and MH of the materials in the rubber compound of the present invention (INV4) are all higher than those in the reference rubber compounds (RIF6 and RIF7).

Claims

1. A compound represented by formula (II): WF-O-ROS-GC-Fe(II) wherein WF represents a white filler, O represents one or more oxygen bridges, ROS represents an organo-silane residue, GC represents one or more coordinating groups that form a chelate with the ionic form of iron, and Fe represents the ionic form (Fe 3+ ) of iron.

2. A method for preparing a compound of formula (II) according to claim 1, wherein the method at least comprises: Provide white filler (WF), Providing a coupling agent having the following formula (I): GR-ROS-GC(I) wherein GR represents one or more reactive groups capable of forming an oxygen (—O—) bridge with the surface of the white filler, ROS represents an organo-silane residue, and GC represents one or more coordinating groups, Provided in ionic form (Fe 3+ ) of the iron precursor, reacting a white filler (WF) with one or more reactive groups (GR) of the compound of formula (I) to form an oxygen (—O—) bridge between the white filler and the organo-silane residue (ROS), · Make one or more coordinating groups (GC) of the compound of formula (I) and ionic form (Fe 3+ ) to form a chelate, and • Isolate the obtained compound of formula (II) WF-O-ROS-GC-Fe.

3. The compound according to claim 1 or the process according to claim 2, wherein the white filler WF is selected from silica and silicates in the form of fibers, flakes or particles.

4. The compound or process according to claim 3, wherein the white filler WF is selected from bentonite, nontronite, beidellite, volkonite, hectorite, saponite, sauconite, vermiculite, sericite, sepiolite, palygorskite also known as attapulgite, montmorillonite, halloysite, etc., which may be modified and / or derivatized by acid treatment, and mixtures thereof.

5. The compound according to claim 1 or the method according to claim 2, wherein the coordinating group (GC) is a straight or branched alkyl chain containing one or more heteroatoms inside or at the end of the alkyl chain.

6. The compound or method according to claim 5, wherein the coordination group GC is of the formula -C n H 2n -XC m H 2m -Y or -C m H 2m -A functional group represented by Y, wherein n and m are the same as or different from each other and are integers from 1 to 6, inclusive, X is a group selected from thiol and amino, and Y is a group selected from thiol, amino, dithiocarbamate and carboxyl.

7. The method according to claim 2, wherein the reactive group GR is an alkoxy group having 1 to 4 carbon atoms.

8. The method according to claim 2, wherein the coupling agent is represented by the general formula (Ia) or (Ib): (R)3Si-C n H 2n -X-C m H 2m -Y(Ia) <h2 style=";text-align:left;direction:ltr">(R)3Si-C<h2 style=";text-align:left;direction:ltr"> m <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 2m <h2 style=";text-align:left;direction:ltr"> -Y(Ib) wherein the R groups are the same as or different from each other and are selected from alkyl or alkoxy groups having 1 to 4 carbon atoms, provided that at least one of the R groups is an alkoxy group; n and m, which are the same as or different from each other, are integers from 1 to 6, inclusive; X is a group selected from thiol and amino, and Y is a group selected from thiol, amino, dithiocarbamate and carboxyl.

9. The method of claim 2, wherein the coupling agent is selected from the group consisting of (3-aminopropyl)triethoxysilane (APTES), N-(2-aminoethyl)-3-aminopropyl-trimethoxysilane (also known as N-[3-(trimethoxysilyl)propyl]ethylenediamine (EDTMS)), N-(2-aminoethyl)-3-aminopropyl-triethoxysilane, N-(2-aminoethyl)-3-aminopropyl-methyl-dimethoxysilane, 3-aminopropylmethyl-diethoxysilane, 3-ureidopropyl-trimethoxysilane, 3-ureidopropyl-triethoxysilane, N-cyclohexyl(aminomethyl)methyldiethoxysilane, N-cyclohexyl(aminomethyl)triethoxysilane, N-cyclohexyl-3-aminopropyl-trimethoxysilane, 3-(2-aminomethylamino)propyl-triethoxy Silane, N-(n-butyl)-3-aminopropyltrimethoxy-silane, N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-aminoisobutyl-methyldimethoxysilane, 3-aminopropylmethyldimethoxysilane, 3-(2-(2-aminoethylamino)ethylamino)propyl-trimethoxysilane, N-(n-butyl)-3-aminopropyl-triethoxysilane, N,N-diethylaminopropyl-trimethoxysilane, N,N-dimethylaminopropyl-trimethoxysilane, butylaminomethyl-triethoxysilane, N-cyclohexyl(aminomethyl)trimethoxysilane, 2-aminoethylaminomethyl-triethoxysilane, diethylaminomethyl-triethoxysilane, (3-mercaptopropyl)triethoxysilane and (3-mercaptopropyl)trimethoxysilane.

10. The method of claim 9, wherein the coupling agent is selected from (3-mercaptopropyl)trimethoxysilane, (3-aminopropyl)triethoxysilane (APTES), (3-aminopropyl)trimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane (also known as N-[3-(trimethoxysilyl)propyl]ethylenediamine (EDTMS)) and N-(2-aminoethyl)-3-aminopropyltriethoxysilane.

11. The method according to claim 2, wherein the ionic form (Fe 3+ ) is selected from iron oxide (Fe2O3), iron hydroxide (Fe(OH)3) and Fe 3+ of organic or inorganic salts.

12. The method according to claim 11, wherein the organic or inorganic salt of iron is selected from ferric nitrate, ferric sulfate, ferric carbonate, ferric chloride, ferric bromide, ferric iodide, ferric fluoride, ferric phosphate, ferric acetate, ferric oxalate, ferric citrate, ferric gluconate, ferric fumarate and ferric lactate.

13. A method for preparing a vulcanizable elastomeric rubber compound for a tire, wherein the method comprises at least: a mixing step (1) of at least one elastomeric polymer and at least one additive other than a vulcanizing agent for an elastomeric compound, in order to obtain a non-vulcanizable elastomeric compound; a mixing step (2) of said non-vulcanizable elastomeric compound and at least one vulcanizing agent to obtain a vulcanizable elastomeric compound, and a step of unloading said vulcanizable elastomeric compound, wherein in at least one of the mixing steps (1) and (2) The compound of formula (II) according to claim 1.

14. Vulcanizable elastomeric compound obtainable by the process according to claim 13.

15. A tire component comprising the vulcanizable rubber compound according to claim 14 or a vulcanized rubber compound obtained by vulcanizing the same.

16. A tyre for a vehicle wheel, comprising the component according to claim 15.

Citation Information

Patent Citations

  • Process for preparing compounds for tyres and tyres comprising them

    WO2020110023A1

  • Process for preparing compounds for tyres and tyres comprising them

    CN113165424A

  • Tyre for vehicle wheels, tread band and elastomeric composition used therein

    US20050155687A1

  • Process for preparing compounds for tyres and tyres comprising them

    US20220010104A1

  • Process for treating particles, and their use in dispersions

    WO2000031175A1